Dinamika sejarah lahirnya Pancasila: Pertentangan gagasan dan politik dalam lahirnya Pancasila - Nur Khosimah, Dina Lailatun (Maliki Interdisciplinary Journal, 2025)
After Indonesia gained its independence, national figures began to formulate a national foundation that would serve as a guideline for all Indonesians. Pancasila was created through several stages of negotiation, delivered by many of the nation’s founding fathers. Pancasila did not emerge instantly. Instead, it emerged as the result of a long historical period filled with ideological and political obstacles among the nation’s founders. Ultimately, they all agreed on the foundation of the Indonesian state. The purpose of this paper is to examine the various differences in ideas and political interests that emerged during the process of formulating Pancasila during the BPUPKI session in 1945. This includes obstacles regarding the Jakarta Charter and the agreement and approval of the PPKI session. Starting from the ideological differences of the nation’s founders, particularly between the nationalist (nationalist) and religious (religious) groups, ideas and political references emerged that led to the formation of Pancasila. During this process, clashes occurred between three main groups: nationalists, Muslims, and communists.